Peningkatan hasil belajar matematika materi menggunakan pecahan dalam pemecahan masalah dengan pendekatan Contextual Teaching Learning (CTL) - Asrial Asrial (Indonesian Counselor Association (IKI), 2019)
Learning mathematics using fractions in problem-solving is boring for students. For this reason, researchers are interested in improving the process of learning mathematics, especially learning Using Fractions in Problem Solving with the Contextual Teaching Learning (CTL) approach. The CTL approach is felt to be able to overcome the existing problems. This study aims to describe the planning, implementation, and assessment of mathematics learning outcomes improvement using fractions in problem-solving with a contextual approach. The implementation of this research uses a qualitative and quantitative approach using a class action research design which includes: (1) Planning, (2) Implementation, (3) Observation and (4) Reflection. The study was conducted in 2 cycles. Research data in the form of information about the process and action data obtained from observations, test results, discussions and documentation. Research subjects consisted of Class V students totaling 20 students. The average percentage of completeness of learning outcomes in research conducted in the first cycle of meeting 1 was 60%, in cycle I meeting 2 was 70%, the average learning outcomes in cycle II meeting 1 was 80%, in cycle II meeting 2 was 90%. The conclusion obtained from this study is the CTL approach can improve learning outcomes Using Fractions in Problem Solving, namely about multiplication and division of fractions.